2015
DOI: 10.1111/ane.12422
|View full text |Cite
|
Sign up to set email alerts
|

Case‐fatality and disability in the Tanzanian Stroke Incidence Project cohort

Abstract: ObjectivesThe burden of stroke on healthcare services in sub‐Saharan Africa (SSA) is increasing. However, long‐term outcomes from stroke in SSA are not well described. We aimed to investigate case‐fatality and health outcomes for stroke survivors at 7‐ to 10‐year follow‐up.Materials and methodsThe Tanzanian Stroke Incidence Project (TSIP) recruited incidence stroke cases between 2003 and 2006. We followed up cases in 2013, recording date of death in those who had died.ResultsOf 130 stroke cases included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…These findings could be explained by the duration of the disease; longer periods of time since the onset of stroke were associated with better acceptance of disability [85]. Most of the individuals investigated in prior studies with better SRH had mild disabilities [48] and higher survival rates [86]. In their qualitative study, Mavaddat et al [42] reported that the severity of physical limitations alone did not influence perceptions of SRH; even individuals with severe morbidities could report good SRH.…”
Section: Discussionmentioning
confidence: 99%
“…These findings could be explained by the duration of the disease; longer periods of time since the onset of stroke were associated with better acceptance of disability [85]. Most of the individuals investigated in prior studies with better SRH had mild disabilities [48] and higher survival rates [86]. In their qualitative study, Mavaddat et al [42] reported that the severity of physical limitations alone did not influence perceptions of SRH; even individuals with severe morbidities could report good SRH.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most assessments are insensitive to ne motor skills, known as the ceiling effect, and fail to respond to the recovery of UE function in patients in the later periods of rehabilitation [20]. These limitations of the assessment scales probably result in non-selective and targeted rehabilitative training [21,22]. Therefore, an objective and sensitive assessment of UE motor function is necessary for rehabilitation at home.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the factors cited as contributing to the increased risk of death include stroke severity, functional disability, high blood pressure, increasing age, dysphagia, and infections such as pneumonia [ 7 , 8 , 9 ]. Low survival rates after ischemic stroke have been attributed to lack of access to acute management of strokes, socioeconomic factors, and variations in geographic locations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%